Implementation of Gender and Ecology Mainstreaming Policies at Sekolah Penggerak and Eco Green Schools in Surabaya: Ecofeminism Study - Hendarwati, Endah; Setiyawan, Radius; Ichda Wahyuni, Holy; Budiman, Agus; Uswatun Hasanah, Siti; Azmi Fauzia, Faiz; Rahayu Roisiah, Riska; Nastainul Firdaus, Akhlis (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This research aims to discuss the implementation of gender and ecology mainstreaming policies in Sekolah penggerak in elementary schools and eco-green schools in Surabaya through an ecofeminist approach. This research uses a qualitative multi-case study approach, with the research subjects being four schools, namely SD Negeri 2 Benowo, SD Muhammadiyah 4 Surabaya, SD Al Khairiyah Surabaya, and SD Kristen Kalam Kudus Surabaya. The research results show that schools with the Adiwiyata or similar labels can better implement ecological awareness programs such as green and eco-green schools. They adopt programs such as hydroponics, recycling, and zero-waste healthy canteens and integrate them into the curriculum with relevant themes. Apart from that, these schools also apply the principles of gender-oriented, child-friendly schools. This research examines how gender mainstreaming and ecology are practised in schools. Both in the form of policies, learning design and related infrastructure. The results of this research illustrate that although there has been progress in implementing gender mainstreaming and ecology policies in schools, further efforts are still needed to increase students' understanding and awareness of these issues. In some aspects, gender and ecological approaches still seem symbolic and insubstantial.